Effects of process approach in developing the writing skills of college freshmen students - Paug, Marvi S. (2008)
This study aimed to develop the skills of college freshmen students in both expository and argumentative writing tasks through the process approach of teaching. The process approach consists of prewriting, writing, revising, and editing without having the students to consciously focus on grammatical conventions. It was tested for three months on eighty college freshmen students. One group was assigned as the experimental group and underwent enrichment activities through various forms of intervention in the writing process. Students in the control group were given the same writing tasks without the process approach in writing. Results showed that students in the experimental group showed marked improvement in both expository and argumentative tasks while those in the control group only showed minimal improvement. The process approach was effective in developing the writing skills of college freshmen students.